The city in Texas : a history - McComb, David G. (Bridwell Texas history series., 2015)
"This book is the first history of cities in Texas, covering the earliest days of Spanish-Mexican towns, the Republic era to about 1940, and metropolitan Texas to the present. Not only is this book a first for Texas, but there seem to be no equivalent books for any other states, so the author has developed new concepts like 'the first road frontier' and the 'rupture' caused by the railroads. McComb emphasizes how railroads and related innovations such as the telegraph and the clock facilitated in urban development"--Provided by publisher.